Increased cFLIP expression in thymic epithelial tumors blocks autophagy via NF-κB signalling - Belharazem, Djeda (Oncotarget, 2017)
The anti-apoptotic cellular FLICE-like inhibitory protein cFLIP plays a pivotal role in normal tissues homoeostasis and the development of many tumors, but its role in normal thymus (NT), thymomas and thymic carcinomas (TC) is largely unknown. Expression, regulation and function of cFLIP were analyzed in biopsies of NT, thymomas, thymic squamous cell carcinomas (TSCC), thymic epithelial cells (TECs) derived thereof and in the TC line 1889c by qRT-PCR, western blot, shRNA techniques, and functional assays addressing survival, senescence and autophagy. More than 90% of thymomas and TSCCs showed increased cFLIP expression compared to NT. cFLIP expression declined with age in NTs but not in thymomas. During short term culture cFLIP expression levels declined significantly slower in neoplastic than non-neoplastic primary TECs. Down-regulation of cFLIP by shRNA or NF-κB inhibition accelerated senescence and induced autophagy and cell death in neoplastic TECs. The results suggest a role of cFLIP in the involution of normal thymus and the development of thymomas and TSCC. Since increased expression of cFLIP is a known tumor escape mechanism, it may serve as tissue-based biomarker in future clinical trials, including immune checkpoint inhibitor trials in the commonly PD-L1(high) thymomas and TCs.